Assessment of eight rice cultivars flour for feeding resistance to Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). (September 2020) - Naseri, Bahram; Majd-Marani, Shadi
Abstract: Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) is an important pest of processed stored grains worldwide. Study of life history, feeding efficiency and digestive function of an insect on different host cultivars can indicate their resistance for the insect's population increase. Due to the economic importance of T. castaneum on stored rice flour, this research was aimed to investigate the life history, feeding indices and digestive enzymatic activity of T. castaneum on flour of eight rice cultivars (Ali-Kazemi, Dom-Siah, Fajr, Gilaneh, Gohar, Hashemi, Khazar, and Neda). A delay in the developmental time of T. castaneum was detected on cultivar Gohar. The lowest fecundity and egg fertility were observed on cultivar Gohar. Feeding indices of fourth instar larvae were the lowest on cultivars Gohar and Neda. The amylolytic activity of fourth instar larvae was the highest on cultivars Hashemi, Dom-Siah, Ali-Kazemi and Gilaneh, and the lowest on cultivar Gohar. Also, the highest and lowest proteolytic activities of fourth instar larvae were on cultivars Khazar and Hashemi, respectively. Significant correlations were detected between tested parameters of T. castaneum with starch and protein value of examined cultivars flour. The results of cluster analysis indicate that Dom-Siah, Hashemi and Ali-Kazemi are relatively susceptible cultivars, and other tested cultivars, especially Gohar, are relatively resistant cultivars for feeding of T. castaneum . The resistant rice cultivars could be further evaluated to identify secondary biochemicals that contribute to T. castaneum resistance. Graphical abstract: Image 1 Highlights: Tribolium castaneum is one of the polyphagous postharvest pests of cereal grains. A delay in the developmental time of T. castaneum was detected on cultivar Gohar. The lowest feeding indices were detected in larvae fed with cultivars Gohar and Neda. The amylolytic activity of larvae was the lowest on cultivar Gohar. Cluster analysis showed that cultivars Gohar, Neda, Fajr, Khazar, and Gilaneh were partially resistant to T. granarium.